(untitled) (Studia austriaca, 2015)
In Ludwig Wittgensteins’ Philosophical Investigations, physiognomy is used as a metaphor for the impenetrable boundary between the inner character and the outside appearance of language. In his novel Correction Thomas Bernhard confronts this concept of impenetrability with a specific production of architectural space. His protagonist Roithamer is consciously fighting against Wittgensteins boundaries of what is sayable. Both texts reflect the end of the long debates about physiognomics by reconsidering physiognomic thought as an aporetic but still productive hermeneutic tool.